2003
DOI: 10.1002/ange.200351940
|View full text |Cite
|
Sign up to set email alerts
|

First Structurally Authenticated Zinc Alkylperoxide: A Model System for the Epoxidation of Enones

Abstract: β‐Ketoiminliganden stabilisieren Zinkkomplexe: Das dimere Zinkalkylperoxid [{(LL)ZnOOEt}2] (LL=HC{(CMe)(2,6‐iPr2C6H3N)}2) wurde isoliert und strukturell charakterisiert (siehe Bild, Zn grün, N blau, O rot, C grau). Der Komplex, der durch Insertion von Disauerstoff in die Zn‐Et‐Bindung gebildet wird, ist hoch aktiv in der Epoxidierung von Enonen.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
23
0

Year Published

2004
2004
2021
2021

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 43 publications
3
23
0
Order By: Relevance
“…In a control experiment, a solution of [EtZn(O 2 Ph)] n (1) in THF at 0 8C was treated with an excess of dry dioxygen and the reaction mixture was stirred for approximately five minutes. [6] Based upon the reaction outcome and our recent extensive studies on the oxygenation of alkylzinc complexes, it is reasonable to propose the reaction mechanism shown in Scheme 1 as a working hypothesis. The identity of 2 has been confirmed by X-ray crystallography.…”
mentioning
confidence: 95%
See 3 more Smart Citations
“…In a control experiment, a solution of [EtZn(O 2 Ph)] n (1) in THF at 0 8C was treated with an excess of dry dioxygen and the reaction mixture was stirred for approximately five minutes. [6] Based upon the reaction outcome and our recent extensive studies on the oxygenation of alkylzinc complexes, it is reasonable to propose the reaction mechanism shown in Scheme 1 as a working hypothesis. The identity of 2 has been confirmed by X-ray crystallography.…”
mentioning
confidence: 95%
“…[1] Zinc oxocarboxylates with the general formula Zn 4 O(O 2 CR) 6 have been known for decades, [2] and interest in them was renewed in the late 1990s primarily by the work of Yaghi and co-workers, who developed the synthesis of metal-organic frameworks (MOFs) with high porosities and tailor-made molecular cavities based on these oxo clusters as secondary building units (SBU). For instance, zinc carboxylates, and particularly alkoxyzinc carboxylates, are attracting a great deal of attention owing to their importance as highly active catalysts for the polymerization or copolymerization of a wide range of organic monomers.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…[10] Nevertheless,despite continuous interest in this area, the well-defined Zn-catalyzed highly enantioselective epoxidation of enones remains elusive.In1996, Enders et al [11] reported the first stoichiometric asymmetric epoxidation of a,b-unsaturated ketones mediated by aZ na lkyl peroxide,w hich was generated in situ from Et 2 Zn, (R,R)-N-methylpseudoephedrine and O 2 .U nder such conditions, transchalcone epoxidation was completed in 16 hw ith 61% ee.S ince then, various structurally ill-defined Zn catalysts possessing aB INOLm oiety in combination with tert-butyl hydroperoxide (TBHP) or cumene hydroperoxide (CMHP) have been developed for the catalytic asymmetric epoxidation of av ariety of enones,p roviding the corresponding epoxides in good yields andw ith very high enantiomeric excesses up to 96%. [5a-d] In 2003, our group reported the first structurally authenticated Zn alkyl peroxides [12] and demonstrated that one of them, namely [(BDI)ZnOOEt] 2 (BDI = bdiketiminate ligand), exhibits high efficiency in the stoichiometrice poxidation of trans-chalcone.…”
mentioning
confidence: 99%